Ready–Willing–Able: Early childhood mortality decline in Turkey. (4th May 2022) - Aktar, Rengin; Palloni, Alberto
Abstract : We test a conjecture to explain Turkey's decades-long 'underachievement' in early child mortality improvements. We argue that it is largely a consequence of cultural barriers to embracing available modern medical technology and healthcare practices. The empirical test rests on a reformulation of Coale's Ready–Willing–Able (RWA) framework for explaining fertility changes, which makes it suitable to understand mortality changes. We use structural equation modelling and Demographic and Health Surveys spanning 1993–2013 to estimate basic parameters of the reformulated framework. These parameters are then used to classify mothers into four groups with different configurations of RWA dimensions and different probabilities of adopting modern medical practices. We find that observed behaviours in these groups were consistent with RWA expectations. In addition, we find that an important contributor to Turkey's lagging mortality decline was a population distribution biased towards groups more reticent to adopting modern healthcare.